Training implications of changing donor approaches - Fell, Peter; Jacobs, Colin (1999)
In recent months, donors have signalled a desire to move away from the orthodoxy of project aid. Project aid is criticized as being donor led and creating non-sustainable systems. Furthermore, it works outside the main structures of government ministries. In its place the new paradigm calls for sector investment and development programmes which are seen as being more integrated into ministry structures. By making greater demands on those structures, they will create an impetus for lasting change. Training in this context is a facilitating process to ensure that these higher level demands can be met. - Reproduced
Keywords: Training; Foreign aid